Comparative Study of The Amount of Apically Extrusion Of Debris During Root Canal Preparation Using Wave One™, Trushape 3D™, Hyflex™ CM and One Shape™ Instrumentation Systems (An In Vitro Study) - Ali W. Hadi; Mohammed R. Hameed (College of Dentistry/ University of Baghdad, 2017)
Background: Many types of instruments and techniques are used in the instrumentation of the root canal system. These instruments and techniques may extrude debris beyond the apical foramen and may cause post-instrumentation complications. The aim of this study was to evaluate the amount of apically extruded debris resulted by using 4 types of nickel-titanium instruments (WaveOne, TRUShape 3D conforming files, Hyflex CM, and One Shape files) during endodontic instrumentation. Materials and methods: Forty freshly extracted human mandibular second premolar with straight canals and a single apex were collected for this study. All teeth were cut to similar lengths. Pre-weighted glass vials were used as collecting containers. Samples were randomly divided into four groups with 10 samples in each group: Group A instrumentation by WaveOne reciprocating file, Group B instrumentation by TRUShape 3D rotating files, Group C instrumentation by Hyflex CM rotating files and Group D instrumentation by One Shape rotating file. A total volume of 7 ml of sodium hypochlorite was used for irrigation in each sample. Apical patency confirmed and maintained by a size #15 K-File. All canals were instrumented up to a size #25. After completion of endodontic instrumentation, vials were then stored in an incubator for 5 days at 68o C for dryness. Then vials are weighted again, and the pre-weight subtracted from the post-weight, the weight difference resembled the amount of apically extruded debris from the apical foramen during root canal instrumentation. Data obtained were statistically analysed by using ANOVA and LSD tests. Results: The results showed that the Hyflex CM Group (C) has statistical significant lowest apically extruded debris as compared to other groups of this study (P ≤0.05), while the TRUShape Group (B) has statistical significant lowest apically extruded debris as compared to One Shape Group (D) and WaveOne Group (A), while the WaveOne Group (A) showed the highest value of apically extruded debris (p ≤0.01). The result showed that all groups resulted in apical extrusion of debris. Significance: Although all systems caused apical extrusion of debris and irrigant, continuous rotary instrumentation was associated with less extrusion as compared with the use of reciprocating file system.